Exploring the Role of Servant Leadership in Human Resource Development: A Case Study of the Leadership Performance at Talenta Sejahtera Bersama Cooperative - Nitte, Eka Putri; Andjarwati, Tri; Ardiana, Dewa Ketut Raka (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study aims to explore the role of servant leadership in the human resource development (HRD) process and its implications for leadership performance at the Talenta Sejahtera Bersama Cooperative in Kota Kupang. The research focuses on how the application of servant leadership values supports sustainable HR development strategies and contributes to improved organizational performance. A qualitative approach using a case study method was employed. Data were collected through in-depth interviews with key informants, including the general manager, HR manager, branch managers, senior and junior employees, and cooperative members from both the central and branch offices. Thematic analysis was conducted to identify patterns related to three main aspects: (1) the implementation of servant leadership by cooperative leaders, (2) the management of human resource development, and (3) the contribution of servant leadership to employees' work experiences and motivation. The findings indicate that the application of servant leadership fosters an inclusive and supportive work environment grounded in service-oriented values. Leaders who practice servant leadership demonstrate a strong commitment to listening, nurturing, and empowering employees. HR management is carried out in a participatory manner and focuses on competency development, ultimately contributing to increased performance and employee loyalty. These findings affirm that servant leadership is not only an ethical leadership model but also a strategic approach to achieving sustainable organizational performance.